Literary Reception in Tere Liye's Novel Rembulan Tenggelam di Wajahmu (Aesthetic Studies of Experimental Reception) - Rahmatul Zahra, Fareha; Suta Wardianto, Bayu; Anggraini Diwansyah, Fitria; Hadiansyah, Firman (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2023)
Literary works are certainly inseparable from reader responses where a comment/response can show the quality of a work. The activity of commenting in the realm of literary studies is referred to as a literary reception. This study describes readers responses based on readers criteria for novel Rembulan Tenggelam di Wajahmu by Tere Liye , and the aesthetic assessment of the reception to the novel based on Hans Robert Jauz's theory. The research method used is qualitative method, where data is collected using questionnaires distributed through Google Form. The collected data is then analyzed with comparative descriptive techniques. Based on his responses, the criteria were highly assessed, namely the selection of characters in the novel, the idea or theme of the story, new perspectives, emotional involvement, narrative techniques, sadness, and universality. The criteria assessed are moderate, namely attraction, plot,, tempo, understandable, intrinsic elements, imagery, plausible, ironic, conflict, and characters. Finally, the criteria that are considered the lowest, are further interest and language style.